Change in Japanese children’s 24-hour movement guidelines and mental health during the COVID-19 pandemic - Kim Hyunshik (Nature Portfolio, 2021)
Abstract Specialized guidelines are required for the health behaviors of vulnerable populations such as children. This is especially true during the COVID-19 pandemic, wherein major lifestyle changes have occurred, especially among young children. The present study aims to use longitudinal data to understand changes in the physical activity, screen time, sleep, and mental health of preschoolers in Japan during the COVID-19 pandemic, compared to pre-pandemic period. Subjective and objective measures were used to assess the variables of interest longitudinally. It was found that physical activity, adherence to WHO-recommended screen time, and prosocial behaviors decreased significantly. On the other hand, sedentary time and hyperactivity increased. Our results are consistent with findings from other countries. The implications with respect to outdoor playtime, screen-time in the context of online learning during the pandemic, and the effects of parents’ mental health on preschool-aged children are discussed.